2021
DOI: 10.5194/cp-17-1973-2021
|View full text |Cite
|
Sign up to set email alerts
|

Extending and understanding the South West Western Australian rainfall record using a snowfall reconstruction from Law Dome, East Antarctica

Abstract: Abstract. South West Western Australia (SWWA) has experienced a prolonged reduction in rainfall in recent decades, with associated reductions in regional water supply and residential and agricultural impacts. The cause of the reduction has been widely considered but remains unclear. The relatively short length of the instrumental record limits long-term investigation. A previous proxy-based study used a statistically negative correlation between SWWA rainfall and snowfall from the Dome Summit South (DSS) ice c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Another key point is that the climate of the last 100 years may have been the wettest in the past 800 years (O'Donnell et al, 2021), thus potentially facilitating tree encroachment onto shallow soil areas. Now, during one of the driest periods in 2,000 years (Zheng et al, 2021), observed die-off likely reflects these trees reaching a critical threshold in shallow soils. Another way to think of this is that the critical soil thickness is increasing and expanding outwards from areas with shallow bedrock, due to the drying and warming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key point is that the climate of the last 100 years may have been the wettest in the past 800 years (O'Donnell et al, 2021), thus potentially facilitating tree encroachment onto shallow soil areas. Now, during one of the driest periods in 2,000 years (Zheng et al, 2021), observed die-off likely reflects these trees reaching a critical threshold in shallow soils. Another way to think of this is that the critical soil thickness is increasing and expanding outwards from areas with shallow bedrock, due to the drying and warming.…”
Section: Discussionmentioning
confidence: 99%
“…While chronic drying may, in part, be a component of a much longer natural variability (O'Donnell et al, 2021), only two other droughts of similar duration and intensity have occurred in southwest Australia over the last 2,000 years (Zheng et al, 2021). With the future projections for southwestern Australia describing further climate drying and warming, we expect die‐off events will accelerate and expand to include more locations of forest in vulnerable, shallow soil areas (Hope et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on the Law Dome ice core trace chemistry record has indicated that there are strong teleconnections between the southern Indian Ocean climate and Australian hydroclimate . The Law Dome snow accumulation record (Roberts et al, 2015) has been used to reconstruct rainfall across southwest Western Australia, indicating that current drying in the region is unusual but not unprecedented over the past 2000 years (Zheng et al, 2021;van Ommen and Morgan, 2010). Similarly, there is a strong correlation between concentrations of aerosol sea salts during summer snowfall at Law Dome with rainfall in eastern Australia (Vance et al, 2013(Vance et al, , 2015Udy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches for determining climate variability using paleoclimate records or reconstructions. Changes in rainfall have been inferred from distant measurements of snow accumulation (Zheng et al, 2021), which is possible because of an anticorrelation between SWWA May-October rainfall and snowfall at Law Dome, Antarctica (van Ommen & Morgan, 2010). Speleothem records, an in situ climate proxy, are found in caves which develop in Tamala Limestone (Geoscience Australia & Australian -3-manuscript submitted to JGR: Atmospheres Stratigraphy Commission, 2017), an eolian carbonate deposited in the Middle to Late Pleistocene, ∼10-250 ka before present (Smith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%